2010
DOI: 10.1111/j.1365-294x.2010.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Seeing red: the origin of grain pigmentation in US weedy rice

Abstract: Weedy forms of crop species infest agricultural fields worldwide and are a leading cause of crop losses, yet little is known about how these weeds evolve. Red rice (Oryza sativa), a major weed of cultivated rice fields in the US, is recognized by the dark-pigmented grain that gives it its common name. Studies using neutral molecular markers have indicated a close relationship between US red rice and domesticated rice, suggesting that the weed may have originated through reversion of domesticated rice to a fera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 47 publications
(198 reference statements)
6
88
1
Order By: Relevance
“…This similarity suggests that Rc alleles from tropical (e.g., SS18-2 and TKN12-2) and temperate (e.g., LD and C9541) weed ecotypes share some evolutionary mechanisms with those from indica and japonica subspecies, respectively, such as selection pressures from temperatures and cropping systems or common gene donors. Exceptions exist for Rc alleles from weedy genotypes in new rice-growing areas, such as US1 (group I) and other U.S. weedy rice lines discussed in detail by Gross et al (2010). However, our research suggests that the dormancy function of SD7-1 alleles in red rice may not vary with their phylogenetic distances but that detection of the dormancy effect can be influenced by the genetic backgrounds and/or experimental methods.…”
Section: Red Rice-beyond a Pigment Issuementioning
confidence: 65%
“…This similarity suggests that Rc alleles from tropical (e.g., SS18-2 and TKN12-2) and temperate (e.g., LD and C9541) weed ecotypes share some evolutionary mechanisms with those from indica and japonica subspecies, respectively, such as selection pressures from temperatures and cropping systems or common gene donors. Exceptions exist for Rc alleles from weedy genotypes in new rice-growing areas, such as US1 (group I) and other U.S. weedy rice lines discussed in detail by Gross et al (2010). However, our research suggests that the dormancy function of SD7-1 alleles in red rice may not vary with their phylogenetic distances but that detection of the dormancy effect can be influenced by the genetic backgrounds and/or experimental methods.…”
Section: Red Rice-beyond a Pigment Issuementioning
confidence: 65%
“…However, in every case where the survey included an evolutionary component, the origin of the domestication allele was found to be the japonica subspecies (80,81). As a result, the phylogenies generated from domestication genes showed japonica and indica as a monophyletic group (69,84), consistent with a single origin for allele controlling a domestication trait. In contrast, neutral loci generally recovered a polyphyletic relationship (51,59), and analyses that included O. rufipogon showed that japonica and indica were more closely related to different populations of the wild species than to each other, consistent with multiple origins.…”
Section: Genetic Evidence For Rice Domesticationmentioning
confidence: 73%
“…6). Along with seed shattering and seed dormancy, pericarp pigmentation is not favorably selected during the course of rice domestication (Sweeney and McCouch, 2007;Gross et al, 2010). It is possible that ancient rice farmers used the red pericarp color as a visual cue to discard red rice seeds due to perceived association with inferior grain quality.…”
Section: Discussion Starch Structure Implication To Tweak Cooking Quamentioning
confidence: 99%